Relationships between lower limb muscle characteristics and force-velocity profiles derived during sprinting and jumping - Bellinger, P.; Bourne, M. N.; Duhig, S.; Lievens, E.; Kennedy, B.; Martin, A.; Cooper, C.; Tredrea, M.; Rice, H.; Derave, W.; Minahan, C. (Medicine & Science in Sports & Exercise, 2021)
Purpose: This study aimed to identify the relationships between lower limb muscle characteristics and mechanical variables derived from the vertical (jumping) and horizontal (sprinting) force-velocity-power (FVP) profiles. Methods: Nineteen subelite male rugby league players performed a series of squat jumps and linear 30-m sprints to derive the vertical and horizontal FVP profiles, respectively. The theoretical maximal force (F0), velocity (V0), and power (Pmax) were derived from both the vertical (i.e., vF0, vV0, and vPmax) and the horizontal (i.e., hF0, hV0, and hPmax) FVP profiles. Vastus lateralis (VL), biceps femoris long head, and gastrocnemius medialis (GM) and lateralis muscle fascicle length, pennation angle, and thickness were measured using B-mode ultrasonography. Magnetic resonance imaging was used to calculate volumes of major lower limb muscles, whereas proton magnetic resonance spectroscopy was used to quantify the carnosine content of the GM to estimate muscle fiber typology. Results: Variation in vPmax was best explained by GM muscle fiber typology (i.e., greater estimated proportion of Type II fibers) and VL volume (adjusted r2 = 0.440, P = 0.006), whereas adductor and vastus medialis volume and GM muscle fiber typology explained the most variation in hPmax (adjusted r2 = 0.634, P = 0.032). Rectus femoris and VL volume explained variation in vF0 (r2 = 0.430, P = 0.008), whereas adductor and vastus medialis volume explained variation in hF0 (r2 = 0.432, P = 0.007). Variations in vV0 and hV0 were best explained by GM muscle fiber typology (adjusted r2 = 0.580, P < 0.001) and GM muscle fiber typology and biceps femoris short head volume (adjusted r2 = 0.590, P < 0.001), respectively. Conclusion: Muscle fiber typology and muscle volume are strong determinants of maximal muscle power in jumping and sprinting by influencing the velocity- and force-oriented mechanical variables.